INTERCULTURAL AFFORDANCES IN A GRADE X INDONESIAN ENGLISH TEXTBOOK - Berlina Adinul Quyum Al Falah; Dana Yudha Kristiawan; Abd Rahman (ELITERATE : Journal of English Linguistics and Literature Studies, 2026)
Intercultural understanding has become an essential aspect of English language education because language learning involves the development of linguistic competence as well as the understanding of cultural meanings, values, and diverse perspectives. English textbooks provide learners with opportunities to engage with cultural diversity through textual materials, visual representations, and learning activities. This study examined how intercultural understanding was promoted through Work in Progress: English for Senior High School Grade X. This study employed a qualitative approach using qualitative content analysis to examine textual materials, visual representations, and learning activities related to intercultural understanding. The data were analyzed through identification, categorization, interpretation, and conclusion drawing based on Byram’s (1997) five dimensions: intercultural attitudes, cultural knowledge, interpreting and relating, discovery and interaction, and critical cultural awareness. The findings indicated that the textbook represented both Indonesian and international cultures, with cultural knowledge being the most frequently identified dimension. The potential for promoting intercultural understanding varied across chapters. Chapters 5 and 6 provided the strongest opportunities for interpretation, comparison, and critical engagement, while Chapter 3 showed the weakest intercultural potential. These findings suggest that visual representations, when connected with contextual texts and learning activities, can support learners in interpreting cultural differences and developing intercultural understanding.